Quality Evaluation of Plant-Derived Foods - Oliveira, Ivo Vaz de (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This new MDPI book compiles several manuscript highlighting the complexity of "Quality Evaluation of Plant-Derived Foods". It should be of interest for students, researchers, and professors, as important data and methodologies are presented. Results available include not only fruit and plant characteristics, but also by-products valorization and pre-harvest application of coumpounds for fruit and plant quality.